Synthesis and Electronic Properties of Tris(4-Formylbiphenyl-4-Yl) Amine as a Building Block for Covalent Organic Frameworks and for Optoelectronic Devices - Fernández, Mara A.; Zuluaga, Fabio; Chaur, Manuel N. (Revista de Ciencias, 2013)
Herein is reported the preparation of a new triphenylamine derivative, the tris(´4-formylbiphenyl-4-yl) amine (TFBA). This compound exhibits optoelectronic properties suitable for its use in Dye-Sensitized Solar Cells (DSSCs) and light emitting diodes. The electrochemical properties were studied by cyclic voltammetry (CV) and square wave voltammetry (SWV). At the same time, the symmetrical chemical structure of TFBA allows its utilization as a building block in Covalent Organic Frameworks (COFs) bringing additional properties and a wide range of applications to such materials.